USING A SELF-CONTROL TRAINING PROCEDURE TO INCREASE APPROPRIATE BEHAVIOR - Dixon, Mark R.; Hayes, Linda J.; Binder, Lisa M.; Manthey, Sharon; Sigman, Connie; Zdanowski, Darlene M. (Journal of applied behavior analysis, 1998)
The present study evaluated a technique for teaching self‐control and increasing desirable behaviors among adults with developmental disabilities. Results showed that when participants were initially given the choice between an immediate smaller reinforcer and a larger delayed reinforcer, all participants repeatedly chose the smaller reinforcer. Concurrent fixed‐duration/progressive‐duration reinforcement schedules then were introduced in which initially both the smaller and larger reinforcers were available immediately. Thereafter, progressively increasing delays were introduced for the schedule associated with the larger reinforcer only. When initial short‐duration requirements for access to the larger reinforcer were gradually increased, participants repeatedly selected the larger reinforcer, thereby demonstrating increased self‐control.